Carbon based electrodes for application in solar cells - Ong, Jie Yi. (2009)
This project focuses on the investigations of optimizing the single-walled carbon nanotubes (SWCNTs) thin films properties for the application in solar cells. The films were optimized to fabricate carbon based electrodes with properties as good as or better than ITO glass. Studies on the correlation of structural or chemical modification to the electrical properties of carbon nanotubes (CNTs) were also done. CNT solutions were synthesised with the aid of probe sonication and centrifugation and then sprayed coated on glass substrates using the air brush technique to form CNT thin films. The properties of these films were characterised with four-point probe, UV-VIS-NIR Spectrometer, Raman Spectrometer, Atomic Force Microscopy (AFM) and FE-SEM. Films were subsequently fabricated into solar cell devices. Investigations showed that the optimum formulation and synthesizing condition of CNT solution is a 0.1mg/ml ethanol solution with 30 minutes of sonication. Acid treatment of the films with H2SO4 resulted in a 63.6% reduction of the sheet resistance. The mechanism behind this drastic reduction of sheet resistance was found to be due to chemical functionalisation of the SWCNTs. The best efficiency of the solar cell devices fabricated based on these films was 0.3%. Low efficiency obtained was mainly attributed to shorting of the devices. Optimization of the active layer could be a possible way of rectifying this problem.